2017
DOI: 10.1111/ibi.12458
|View full text |Cite
|
Sign up to set email alerts
|

The point of a Guillemot's egg

Abstract: The adaptive significance of avian egg shape in birds is poorly understood. The pyriform (pear‐like) shape of the Common Guillemot's Uria aalge egg has long been considered to be an adaptation to prevent eggs rolling off the bare cliff ledges on which this species breeds. Rolling was thought to be prevented either by the egg spinning like a top, which is not the case, or by rolling in an arc, which it does but with little influence on whether the egg will fall from a ledge. We therefore sought alternative expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 29 publications
2
69
0
1
Order By: Relevance
“…Empirical observations confirm that, among naturally incubated Common Murre eggs, fecal contamination of the eggshell is less likely at the blunt end of the egg (Birkhead et al 2017b).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Empirical observations confirm that, among naturally incubated Common Murre eggs, fecal contamination of the eggshell is less likely at the blunt end of the egg (Birkhead et al 2017b).…”
Section: Introductionmentioning
confidence: 67%
“…In an earlier paper (Birkhead et al 2017b), we suggested that the pyriform shape might (1) reduce the chance of shell breakage by dissipating the forces of any impact-like an adult landing or stepping on the egg-across a wider surface of the shell; or (2) help to keep the blunt pole of the egg (where the embryo's head and the air cell are located) relatively free from debris and fecal contamination, allowing the embryo to respire more efficiently, because that region of the egg has a relatively high density of pores. Empirical observations confirm that, among naturally incubated Common Murre eggs, fecal contamination of the eggshell is less likely at the blunt end of the egg (Birkhead et al 2017b).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…He also showed that parental behavior, including keeping the egg between their legs with the blunt end directed away from the bird, was important in keeping the egg on the ledge (Ingold 1980;see also Tschanz 1990;Ingold 2016). Elsewhere, we consider several other hypotheses for the pyriform shape of guillemot eggs (Birkhead et al 2017). …”
Section: Discussionmentioning
confidence: 99%